Penerapan Media Qestion Card dalam Model Pembelajaran Problem-Based Learning untuk Meningkatkan Kualitas Pembelajaran - Kholipah, Nur; Surindra, Bayu; Forijati, Rr (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2022)
Problem Based Learning model in using the Question Card media which is a learning model. The purpose of this study is to describe the increase in activity and learning outcomes. This research method uses classroom action research. The results of the study were seen from the pra-cycle, cycle I, cycle II the results of student activity included aspects of visual activity the pra-cycle 86,67% cycle I 93,33% cycle II 100%, oral activity pra-cycle 86,67% cycle I 100% and cycle II 100%, listening activity pra-cycle, cycle I, cycle II 93,33%, writing activity the pra-cycle 86,67% cycle I 100%, cycle II 100%, drawing activity the pra-cycle 93,34% cycle I 100% and cycle II 100%, emotional activity the pra-cycle 86,67% cycle I 100% and cycle II 100%, mental activity the pra-cycle 86,67% cycle I 90% cycle II 93,34%. Pra-cycle learning outcomes 87,966 cycle I 90,167cycle II 90,567. The application of Question Card media in the application of Prablem Based Learning including activeness and learning outcomes.